Efficacy of iron supplementation in patients with inflammatory bowel disease treated with anti-tumor necrosis factor-alpha agents - Su Young Kim; Sejin An; Dong Kyun Park; Kwang An Kwon; Kyoung Oh Kim; Jun-Won Chung; Jung Ho Kim; Yoon Jae Kim (Therapeutic Advances in Gastroenterology, 2020)
Background: Anemia is a common extraintestinal manifestation of inflammatory bowel disease (IBD). However, data on the influence of anti-tumor necrosis factor-alpha (anti-TNF-α) agents and iron supplementation on anemia in patients with IBD are sparse. We assessed the effect of iron supplementation in patients with IBD initially treated with an anti-TNF-α agent. Methods: Data from 79 IBD patients who started anti-TNF-α treatment at a tertiary hospital were analyzed. The patients were divided into the anti-TNF-α ( n  = 52) and anti-TNF-α with iron supplementation ( n  = 27) groups. Effects on laboratory parameters, the prevalence of anemia, and disease activity were evaluated at baseline (year 0) and 1 year later. Results: The hemoglobin (Hb) level significantly increased between years 0 and 1 in both groups [12.0 ± 1.8–13.3 ± 2.0 g/dL in the anti-TNF-α group ( p  < 0.001) and 9.8 ± 2.4–11.7 ± 2.3 g/dL in the anti-TNF-α and iron supplementation group ( p  = 0.004)]. In a subgroup analysis of severely anemic patients with IBD, iron supplementation increased the magnitude of the improvement in Hb level (8.5 ± 1.5–11.4 ± 2.1 g/dL; p  = 0.001) compared with the anti-TNF-α group (9.3 ± 0.8–11.4 ± 2.7 g/dL; p  = 0.081). Disease activity was significantly improved in both groups at year 1 compared with year 0. Persistent anemia was significantly correlated with severe anemia at baseline ( p  = 0.017). Conclusion: In anemic patients with IBD, anti-TNF-α agents led to clinically meaningful improvements in anemia independent of iron supplementation. Also, iron supplementation could be helpful in severely anemic patients with IBD.